Systematic analyses of murine masculinization processes based on genital sex differentiation parameters. (14th December 2015) - Suzuki, Hiroko; Suzuki, Kentaro; Yamada, Gen
Abstract : Murine reproductive tissues of the external genitalia and perineum develop with remarkably distinctive characteristics in males and females. Although many researches on such mouse organ development have been reported, there are still limited parameters that evaluate the developmental sexual differences of external genitalia and perineum. Furthermore, elucidation of the recent developmental signals for the external genitalia and perineum requires up‐to‐date knowledge of gene functions in reproductive science. To promote researches on reproductive organ formation, establishment of parameters for the androgen‐mediated formation of external genitalia and perineum is essential. In this study, we propose genital sex differentiation parameters (GSDP), a set of developmental parameters based on systematic three‐dimensional tissue reconstruction and cumulative histological analyses. We define the sexual differences of external genitalia and perineum by GSDP through analyzing mouse models, androgen inhibitor‐induced feminization experiments and Mafb mutant mouse with defective urethral differentiation. The urethral parameters displayed prominent reduction by the androgen inhibitor (finasteride) treatment. However, genital tubercle (GT) size parameters were not affected by such treatment. These results indicated that sensitivity to dihydrotestosterone was different between embryonic GT size and urethral formation. Furthermore, we evaluated the extent of urethral defects of Mafb mutant mice by GSDP. Thus, GSDP is a set of useful parameters to define the sexual differences during external genitalia and perineum development. Abstract : Genital sex differentiation parameters (GSDP), a set of embryonic external genitalia developmental parameters were proposed based on three‐dimensional (3D) tissue reconstruction and cumulative histological analyses. We defined sexual differentiation of external genitalia by GSDP through analyzing mouse models and androgen inhibitor‐induced feminization experiments with local androgen measurement by LC‐MS/MS technology.